RANCANG BANGUN PURECOMPUTE PLATFORM E-COMMERCE UNTUK BELANJA LAPTOP BERBASIS WEBSITE - Musyaffa, Ahmad Irfan; Mulki Indana Zulfa; Muhammad Syaiful Alim (Jurnal SINTA: Sistem Informasi dan Teknologi Komputasi, 2024)
The PureCompute Project is an exploration of the design and implementation of an e-commerce platform with a specific focus on laptop sales. The main goal of PureCompute is to provide an optimal online shopping experience, especially for users looking for technology products such as laptops. This report covers the entire development process, starting from needs analysis, system design, technology selection, to the implementation of key features such as login, register, product pages, shopping cart, and authentication and payment systems. The development methodology adopts a software development life cycle and an iterative approach, ensuring flexibility to accommodate changing user requirements. Thus, PureCompute is designed to be responsive to market dynamics and technological advancements. It is expected that PureCompute's positive contribution in providing an efficient and convenient shopping experience will meet the needs of consumers looking for laptops through the e-commerce platform. The success of this project is expected to support and advance the trend of online shopping in the current digital era, through affordable and innovative solutions for technology users.